Health Care Utilization in the Last Year of Life in Parkinson Disease and Other Neurodegenerative Movement Disorders. Issue 6 (December 2022) - McKenzie, Erica D.; Bruno, Veronica A.; Fong, Andrew; Cai, Pin; Earp, Madalene; Camicioli, Richard M.; de Kock, Ingrid; Buttenschoen, Daniela; Sinnarajah, Aynharan; Miyasaki, Janis
Abstract : Background and Objectives: Neurodegenerative movement disorders are rising in prevalence and are associated with high health care utilization. Generally, health care resources are disproportionately expended in the last year of life. Health care utilization by those with neurodegenerative movement disorders in the last year of life is not well-understood. The goal of this study was to assess the utilization of acute care in the last year of life among individuals with neurodegenerative movement disorders and determine whether outpatient neurology or palliative care affected acute care utilization and place of death. Methods: We conducted a retrospective cross-sectional study including health system administrative data in Alberta, Canada, from 2011 to 2017. Administrative data were used to determine place of death and quantify emergency department (ED) visits, hospitalizations, intensive care unit admissions, and outpatient generalist and specialist visits. Diagnoses were classified by 10th revision of the International Classification of Diseases codes. Stata 16v was used for statistical analyses. Results: Among 1439 individuals (60% male), Parkinson disease (n = 1226), progressive supranuclear palsy (n = 78), multiple system atrophy (n = 47), and Huntington disease (n = 58) were the most common diagnoses. The most frequent place of death was in hospital (45.9%), followed by long-term care (36.3%), home (7.9%), and residential hospice (4.0%). Most (64.2%) had >1 ED visit, and 14.4% had >3 emergency department visits. Fifty-five percent had >1 hospitalization, and 23.3% spent >30 days in hospital. Few (2.6%) were admitted to ICU. Only 37.2% and 8.8% accessed outpatient neurologist and specialist palliative care services, respectively. Multivariate logistic regression found the odds of dying at home was higher for those who received outpatient palliative consultation (OR, 2.49, 95% confidence interval [CI], 1.48–4.21, p < 0.001) and were with a longer duration of home care support (OR, 1.0007, 95% CI, 1.0004–1.0009, p < 0.001). Discussion: There are high rates of in-hospital death and acute care utilization in the year before death among those with neurodegenerative movement disorders. Most did not access specialist palliative or neurologic care in the last year of life. Outpatient palliative care and home care services were associated with increased odds of dying at home. Our results indicate the need for further research into the causes, costs, and potential modifiers to inform public health planning.